The Competency Level in Spelling Skills of the Prospective Teachers at the College of Education at Imam Abdulrahman Bin Faisal University - Abdullah Ahmad R Aljenobi (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The current study aimed to identify the level of ability of student teachers at Imam Abdul Rahman bin Faisal University in writing and spelling skills. Methods: The study used the descriptive analytical method to answer the research questions. After listing the necessary skills, a test was designed to measure the spelling writing skills of the student teachers, and it was presented to the research sample. Results: The results of the study showed that the percentage of student teachers' ability is 75.3% in general, and it is below the required level of 90%. The study also used the (T) test for independent groups with the gender variable, the arithmetic mean and the standard deviation, in addition to the one-way analysis of variance test to identify differences according to the variables of specialization and cumulative average. The results also indicated that there were no statistically significant differences at the significance level (α≤0.05). Depending on the variables of gender, specialization and cumulative average. Conclusions: In the light of these results, the study recommended that care should be taken in enhancing the undergraduate students' mastery of spelling writing skills through holding training courses, due to the positive effects it achieves on the student teacher.